2010
DOI: 10.1007/s10561-009-9144-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of the human amniotic membrane as a scaffold in human articular cartilage repair

Abstract: The human amniotic membrane (HAM) is an abundant and readily obtained tissue that may be an important source of scaffold for transplanted chondrocytes in cartilage regeneration in vivo. To evaluate the potential use of cryopreserved HAMs as a support system for human chondrocytes in human articular cartilage repair. Chondrocytes were isolated from human articular cartilage, cultured and grown on the chorionic basement membrane side of HAMs. HAMs with chondrocytes were then used in 44 in vitro human osteoarthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Human amniotic membrane has been applied historically to enhance healing due to its immune privileged and antibacterial properties, along with its ability to modulate inflammation, reduce pain and scarring, and provide a matrix supporting cellular migration and proliferation 15, 16, 17, 18, 19, 20. Recently, multipotent MSCs have also been isolated in placental tissues, including the amnion and chorion layers of the amniotic membrane,21, 22, 23, 24 and these amniotic membrane derived stem cells have demonstrated the ability to regulate immune cells though secretion of various immunomodulatory cytokines 25, 26, 27, 28…”
Section: Introductionmentioning
confidence: 99%
“…Human amniotic membrane has been applied historically to enhance healing due to its immune privileged and antibacterial properties, along with its ability to modulate inflammation, reduce pain and scarring, and provide a matrix supporting cellular migration and proliferation 15, 16, 17, 18, 19, 20. Recently, multipotent MSCs have also been isolated in placental tissues, including the amnion and chorion layers of the amniotic membrane,21, 22, 23, 24 and these amniotic membrane derived stem cells have demonstrated the ability to regulate immune cells though secretion of various immunomodulatory cytokines 25, 26, 27, 28…”
Section: Introductionmentioning
confidence: 99%
“…Human amniotic membrane (HAM) is an important cell scaffold material (Wakitani et al, 1994;Zhang and Chan, 2010). As pointed out by Díaz-Prado et al (2010), HAM is a good cell loading material for repair of cartilage defect. In the present study, human acellular amniotic membrane (HAAM) was used to load BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of these chondrocyte-based techniques is generally quite good (Minas, 2001;Peterson et al, 2000) but in many cases results in the formation of non-hyaline cartilage repair tissue with inferior mechanical properties and limited durability (Pelttari et al, 2009). ACI has several technical limitations: a) obtaining cartilage explants requires an additional surgical intervention, adding to the articular cartilage damage that increases the osteoarthritic process (Marcacci et al, 2002); b) in vitro chondrocyte proliferation must be limited because the capacity to produce stable cartilage in vivo is gradually reduced when cell divisions are increased (Dell´Accio et al, 2001); c) aging reduces the cellular density of the cartilage, which impacts chondrocyte proliferation capacity in vitro (Menche et al, 1998) and the chondrogenic potential of the periosteum (O´Driscoll & Fitzsimmons, 2001), d) cell culture procedures take too long (3 to 6 weeks) and increase the risk of contamination, e) risk of leakage of transplanted chondrocytes from the cartilage defects, f) the effects of gravity causing the chondrocytes to sink to the dependent side of the defect, resulting in an unequal distribution of cells that hampers the homogenous regeneration of the cartilage (Díaz-Prado et al, 2010c;Sohn et al, 2002), g) not the least the reacquisition of phenotypes of dedifferentiated chondrocytes in a monolayer culture (Kimura et al, 1984;Benya & Shaffer, 1982) and h) hypertrophy of tissue (Steinwachs & Kreuz, 2007;Haddo et al, 2004). The use of periosteum membrane poses constraints and the need for wide surgical incision, hypertrophy of the periosteum peripheral implant and its potential for ectopic calcification.…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 99%
“…Amnion allografts are widely applied in ophthalmology, plastic surgery, dermatology, and gynecology (Tejwani et al, 2007;Santos et al, 2005;Rinastiti et al, 2006;Meller et al, 2000;Morton & Dewhurst, 1986). A recent study demonstrated the potential use of the HAM as a scaffold to support human chondrocyte proliferation in cell therapy to repair human OA cartilage (Díaz-Prado et al, 2010c). Experimental studies in animals with synthetic biomaterials showed disappointing results, since after 8 weeks of implantation, all animals suffered ulceration and loss of cartilage (Oka et al, 1997).…”
Section: Scaffoldsmentioning
confidence: 99%